(untitled) (Acta Scientiarum. Biological Sciences, 2026)
This study aimed to document the diversity of amphibians in Lake Cuipari, Loreto, Peru, as baseline information to support conservation strategies and promote sustainable ecotourism. Fieldwork was conducted between August and October using the visual encounter survey method with day and night sampling periods. Each species was photographed (10–20 images) and identified based on morphological traits, consultation with local experts, and validation via AmphibiaWeb and iNaturalist. A total of 17 species were recorded, comprising 13 frogs and three toads from six families of the order Anura, as well as one caecilian (Siphonops annulatus) from the order Gymnophiona. Noteworthy species such as the South American Common Toad (Rhinella margaritifera), the South American Cane Toad (Rhinella marina), and poison frogs (Allobates femoralis, Ameerega trivittata, A. hahneli) highlight the ecological and medical significance of this assemblage, with most taxa classified as “Least Concern” by the International Union for Conservation of Nature and Natural Resources [IUCN] Red List. These findings reveal the exceptional amphibian richness of Lake Cuipari, provide critical baseline data for long-term monitoring, and emphasize the potential of amphibian-focused ecotourism to integrate biodiversity conservation with sustainable community development.